A Comparison of Classifiers for Solar Energetic Events. Issue Volume 12:Issue S325(2016) (30th May 2017) - Barnes, Graham; Schanche, Nicole; Leka, K. D.; Aggarwal, Ashna; Reeves, Kathy
Abstract: We compare the results of using a Random Forest Classifier with the results of using Nonparametric Discriminant Analysis to classify whether a filament channel (in the case of a filament eruption) or an active region (in the case of a flare) is about to produce an event. A large number of descriptors are considered in each case, but it is found that only a small number are needed in order to get most of the improvement in performance over always predicting the majority class. There is little difference in performance between the two classifiers, and neither results in substantial improvements over simply predicting the majority class.